25-Gauge Vitrectomy in Open Eye Injury with Retained Foreign Body. (9th January 2017) - Sborgia, G.; Recchimurzo, N.; Niro, A.; Sborgia, L.; Sborgia, A.; Alessio, G.
Abstract : Purpose . Ocular trauma with retained foreign body is an important cause of visual impairment in working-age population. Clinical status impacts on the timing and planning of surgery. In the last year small gauge vitrectomy has become safer and more efficient, extending the range of pathologies successfully treated. Aims . To evaluate the safety and outcomes in patients with open eye injury with retained foreign body that underwent early 25-gauge vitrectomy. Methods . In this retrospective, noncomparative, interventional case series, we performed 25-gauge vitrectomy on 10 patients affected by open globe injuries with retained foreign body, over 3 years. We analyzed age, wound site, foreign body characteristics, ocular lesions correlated, relative afferent pupillary defect, visual acuity, and intraocular pressure. Follow-up evaluations were performed at 1, 3, and 6 months. According to the clinical status we performed other procedures to manage ocular correlated lesions. Results . The median age of patients was 37 years. The foreign body median size was 3.5 mm (size range, 1 to 10 mm). 25-gauge vitrectomy was performed within 12 hours of trauma. Foreign body removal occurred via a clear corneal or scleral tunnel incision or linear pars plana scleral access. Visual acuity improved in all patients. Endophthalmitis was never reported. Only two cases reported postoperative ocular hypertension resolved within the follow-up. Retinal detachment recurred in one case only. Conclusions . 25-gauge vitrectomy could be considered as early approach to manage open globe injuries with a retained posterior segment foreign body in selected cases with good outcomes and low complication rate.